O potrzebie uwzględnienia rezerw w analizie płynności finansowej przedsiębiorstwa - Duraj Agnieszka Natasza ("About a Need of Reserves Taking into Account in Financial Liquidity of Enterprise", 2005)
The main of this article is to present a problem which concerns the place and role of reserves at the analysis of financial liquidity of enterprise.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1061, s. 68-75